Active Ageing –The EU’s Response To The Demographic Challenge - Wysokińska, Zofia (Comparative Economic Research. Central and Eastern Europe, 2014)
Europe’s demographic problem (an ageing population) is well-known and has been the object of a number of research projects in the EU. As an example of the scale of the problem, the percentage of persons 55 or older in the overall population of the EU was 30% in 2010, and is expected to rise to 37% in 2030. Raising the retirement age – the response implemented in a number of EU Member States in recent years – cannot be considered as a comprehensive solution to the problem. Older persons encounter more difficulties finding employment, even though they possess knowledge and experience which could be valuable in the conduct of economic activities. Recent years have witnessed a growth in the trend toward “active ageing”, which is considered to be ‘a process of optimization of the chances for good health, active participation, and security, in order to improve the quality of life over the passage of time’, a concept closely correlated with the idea of entrepreneurship among the elderly.It can be noted that there is no comprehensive policy supporting entrepreneurship of elderly people in the age of the Ageing Society in Europe. The aim of the paper is to present the foreseen benefits of the development of enterpreneurship of elderly people supporting policy in the EU and in Poland.